Kolaborasi Antar Aktor Dalam Pencegahan dan Penanganan Pelecehan Seksual di Universitas Kristen Satya Wacana: (Collaboration Between Actors in Preventing and Handling Sexual Harassment at Satya Wacana Christian University) - Cintana Amara Sadmoko; Sri Suwartiningsih; Rizki Amalia Yanuartha (JPAI: Jurnal Perempuan dan Anak Indonesia, 2024)
Sexual harassment occurs because of the practice of patriarchal domination. The places that still often dominated by cases of sexual harassment are universities. When the facts case of the sexual harassment were discovered, a policy was issued, that was Regulation of the Minister of Education, Culture, Research and Technology Number 30 of 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education Environments. This policy requires all universities, one of which is UKSW, to form a special task force, namely PPKS. PPKS collaborates with several supporting partners to facilitate the flow of task implementation. Apart from officially authorized actors, there are other media in the form of Instagram accounts which indirectly contribute to the prevention and handling of sexual harassment cases. PPKS and other media that are not officially connected have their respective roles and actions in carrying out their duties. So, this research will be analyzed using Bruno Latour's Actor Network Theory with descriptive qualitative methodology which sees reality as "what is". This research found whether or not there was collaboration between actors in preventing and handling sexual harassment at UKSW. So recommendations emerge to maximize future strategies in preventing and handling cases of sexual harassment. ABSTRAK Pelecehan seksual terjadi karena adanya praktik dominasi patriarki. Tempat yang masih sering didominasi oleh kasus pelecehan seksual adalah perguruan tinggi. Ditemukannya fakta kasus pelecehan seksual maka terbit suatu kebijakan Peraturan Menteri Pendidikan, Kebudayaan, Riset, dan Teknologi Nomor 30 Tahun 2021 tentang Pencegahan dan Penanganan Kekerasan Seksual di Lingkungan Perguruan Tinggi. Kebijakan tersebut mewajibkan seluruh perguruan tinggi salah satunya UKSW untuk membentuk satgas khusus yaitu PPKS. PPKS menjalin kerjasama bersama beberapa mitra pendukung guna mempermudah alur pelaksanaan tugas. Selain aktor resmi yang berwenang, terdapat media lain berupa akun instagram yang secara tidak langsung memiliki kontribusi dalam pencegahan dan penanganan kasus pelecehan seksual. PPKS dan media yang tidak terhubung secara resmi memiliki peranan dan aksi masing-masing dalam pelaksanaan tugas. Maka, penelitian ini akan dianalisis menggunakan Actor Network Theory milik Bruno Latour dengan metodologi kualitatif deskriptif yang melihat realitas sebagai “apa adanya”. Dalam penelitian ini menemukan ada atau tidaknya kolaborasi antar aktor yang terjalin dalam pencegahan dan penanganan pelecehan seksual di UKSW. Sehingga muncul rekomendasi guna memaksimalkan strategi ke depan dalam pencegahan dan penanganan kasus pelecehan seksual.